668 Introduction of a Pre-Operative Assessment Clinic for Elective Procedures in a Renal Replacement Therapy Unit - Analysis of Effect on Cancellation of Procedures. (19th August 2022) - Waldram, R; Ho, GC; Premakumar, Y; Gabor, C; Richards, C; Kumar, A; Colemeadow, J; Kunduzi, B; Clark, K; Oddy, J; Sran, K; Barnett, N
Abstract: Aim: In September 2020, our Renal and Transplant unit introduced a new formalised protocol for Pre-Operative Assessment Clinics (POACs), led by SHO-grade junior doctors. This study aims to investigate the efficacy of the new protocol. Method: All elective operations including dialysis access procedures, transplant urology, parathyroidectomies and hernia repairs conducted by a single renal replacement therapy unit were examined over an 18-month period prior to POAC implementation, then a 12-month period following implementation. Living donor transplants and nephrectomies were excluded. On-the day (OTD) cancellation causes were analysed and categorised into: Predictable patient factors identified in POACs (such as undertreated hypertension and raised inflammatory marker) Unpredictable patient factors (including issues that developed between POAC and admission) Hospital factors (such as lack of bed capacity) Results: Total cases performed: Pre-implementation = 921, post-implementation = 415. OTD cancellations: Pre-implementation - total of 211/921 (22.9%). 90 (9.8%) were due to predictable patient factors, 54 (5.9%) for unpredictable patient factors and 67 (7.2%) for hospital factors. Post-implementation - total of 58/415 (11.6%). 32 (7.7%) for unpredictable patient factors and 12 (2.9%) for hospital factors. Four (1%) were cancelled for predictable patient factors, two due to patients presenting with hypertension. Conclusions: Patients with renal failure have multiple co-morbidities. Optimising pre-operative care is crucial to ensure they receive timely treatment. This audit has demonstrated that a redesigned POAC led to a reduction of OTD cancellation rates from 22.9% to 11.6%, with a marked reduction in predictable causes for cancellations. Further improvements and re-audit are planned.